Tracking the multiple-stage exhumation history and magmatic-hydrothermal events of the West Junggar region, NW China: Evidence from 40Ar/39Ar and (U-Th)/He thermochronology. (15th June 2018) - Yin, Jiyuan; Chen, Wen; Xiao, Wenjiao; Long, Xiaoping; Tao, Ni; Liu, Li-Ping; Yuan, Chao; Sun, Min
Graphical abstract: Highlights: The timing of the main hydrothermal events is constrained by multiple dating methods. There were three episodes of exhumation: 307–277 Ma, 241–232 Ma, 145–120 Ma. Exhumation during the Mesozic was due to collision between Cimmerian blocks. The India-Eurasia collision has had little or no effect on the West Junggar. Abstract: To decipher cooling events in the West Junggar region, biotite and K-feldspar 40 Ar/ 39 Ar, and zircon and apatite (U-Th)/He isotopic analyses of intrusive rocks were carried out. Previous U-Pb data showed that intrusive bodies in the Baogutu area were emplaced at 315–310 Ma. U-Pb and zircon (U-Th)/He dating results (313–241 Ma) suggest that a magmatic-hydrothermal event lasted for 72 Ma in the Baogutu area of the West Junggar region. Early-stage high temperature alteration (900–300 °C) lasted for 6-–2 Ma and was followed by prolonged phyllic and argillic alteration lasting 67–63 Ma between 350 and 200 °C. Finally, slower cooling occurred between 200 and 70 °C, accompanied by post-mineralization uplift and erosion. In this study, three main episodes of relatively rapid cooling were distinguished in the West Junggar region, i.e. late Carboniferous-early Permian (307–277 Ma), middle Triassic (241–232 Ma) and early Cretaceous (145–120 Ma). The first rapid cooling during the late Carboniferous-early Permian was possibly associated with the release of magmatic heat. The middle Triassic and early Cretaceous cooling and exhumation are interpreted as a response to collision(s) between the Qiangtang and Kunlun-Qaidam or Lhasa blocks. The Cenozoic India-Eurasia collision, however, may have had little or no effect on modern tectonic reactivation of the West Junggar region.